High-density lipoprotein cholesterol efflux capacity as a relevant predictor of atherosclerotic coronary disease. Issue 1 (September 2015) - Ishikawa, Tetsuya; Ayaori, Makoto; Uto-Kondo, Harumi; Nakajima, Takatomo; Mutoh, Makoto; Ikewaki, Katsunori
Abstract Background We examined the clinical relevance of high-density lipoprotein cholesterol (HDL-C) efflux capacity from macrophage (cholesterol efflux capacity) as a predictor of atherosclerotic coronary artery disease (CAD) in comparison with that of conventional coronary and lipid risk variables in Japanese daily practice. Methods and Results Fasting blood sampling, including 6 routinely measured dyslipidemia-related variables, was performed at the time of coronary angiography (CAG) or multi-slice coronary computed tomography (MSCT) between January 2011 and January 2013. CAD, defined as native coronary atherosclerosis stenosis >50% by CAG or MSCT, was identified in 182 patients (CAD group), but not in 72 patients (non-CAD group). Cholesterol efflux capacity, measured using a cell-based efflux system in (3)[H]-cholesterol-labeled J774 macrophages in apolipoprotein B-depleted plasma, was significantly impaired in the CAD group compared with the non-CAD group (0.86 ± 0.26 vs. 1.02 ± 0.38; p = 0.001). After adjusting 15 patient and dyslipidemia-related variables using a propensity score matching analysis produced 55 patients in each arm, cholesterol efflux capacity in the CAD group remained to be significant compared with the non-CAD group (0.83 ± 0.24 vs. 0.97 ± 0.36; p = 0.019). Stepwise logistic regression analysis using a backward method after the baseline adjustment showed that cholesterol efflux capacity (odds ratio [OR]: 0.23; 95% confidence interval [CI]: 0.056–0.91; p = 0.037) was the single predictor of CAD, while other variables including HDL-C (p = 0.088) and apolipoprotein (apo) A-I (p = 0.681) were removed owing to those insignificance. The area under the receiver operating characteristic curve after the baseline adjustment was 0.67 (95% CI: 0.51–0.73, p = 0.048 by Hosmer–Lemeshow goodness-of-fit statistics). Conclusions The present observational study conducted under daily clinical practice confirmed that cholesterol efflux capacity is a clinically relevant predictor of CAD among the conventional coronary risk factors and dyslipidemia-related variables.